Evolução dos investimentos no Brasil: uma análise econométrica: por que não houve recuperação das taxas de investimentos no país após a estabilização da inflação em 1994? - Ferreira, João Marcelo Grossi (2006)
Empirical studies on the determinants of private investments in development countries, including several studies in Brazil, have shown that there is a negative impact of high inflation on private investments. However, the recent Brazilian experience shows clearly that stabilization by itself is not sufficient to generate higher investments ratios. The main goal of this thesis is to find empirical evidence that explains why private investment and the investment ratio did not recover after the Real-plan, even though inflation was under control in the 1995-2004 period. In order to achieve this goal econometric estimations were done for long-term private investiments and also of the crowding-out effect of public investments in other areas than infrastructure on private investments. In order to find empirical evidence of the negative impact of both increased government revenues as well as the increase of relative prices of capital goods on private investments since 1995 a model using quarterly data for 1995-2004 was estimated. A more datailed analysis of the Brazilian tax burden and its composition has shown that the tax burden is, not only ever high but also not optimally allocated. Tax revenue comes mainly from taxing production (goods and services) and less from taxing income and property. Moreover, although tax revenue has increased over the last ten years, government spending has become more inefficient, largely in the form of low or non-productive spending while productive government expediture, including government spending on infrastructure, has fallen.